Práticas de finanças solidárias como práticas urbanas: uma análise das ações dos Bancos Comunitários de Desenvolvimento - Gustavo Resgala Silva (2019)
This thesis constitutes an investigation into the possibility of having a proposal for developing emancipatory urban relationships in experiences of social and solidarity economy. Specifically, its purpose is to demonstrate the socio-spatial dimention of the practices of solidarity finances of the Community Development Banks (CDBs), community associations created in more than 100 poor communities in Brazil. The operation methodology of these banks determines them to act in four central points: credit funds, local circulating currency, local producer’s fairs and solidarity economy trainning. This research draws an analytical/investigative way through which the influences of economical process on the production of the city space are explored, focusing on the configuration of the peripheries, in order to demonstrate aspects of the poverty and of the urban identity, of the concept of development and of the socio-economic dynamics into a local/community scale. That leads us to understand that the set of actions of the community banks enable to verify a new economy in its spatial dimension, since they propose a return to the local, to the space produced and lived from initiatives of the community constituted there. Though, beyond the analysis of the methodological approach of the CDBs, this thesis intends to consolidate a critical reading of the experiences of the CDBs as it elaborates and identifies a set of aspects that enable to validate their possible urban meanings. Therefore, it is verified that the practices of the CDBs constitute a complex phenomenon, having interfaces that act on the financial and urban inclusion of the population assisted by them, at the same time that they aim to propose the differentiation of these communities due to their logic in making economy and, thus, of being a city. The illustrations that the field visit provided in order to compose this picture indicate that the aim of financial inclusion has been more evident if compared to the efforts for urban differentiation (and emancipation) of the peripheries studied.